Mechanistic role of miR-375 in regulating PDPK1 to promote progression of small bowel neuroendocrine tumors: a silico analysis - Tao Ren; Lu Zhou; Zhenlong Li; Mingmei Pan; Xueqiong Han (Discover Oncology, 2025)
Abstract Background The incidence of small bowel neuroendocrine tumors (SBNETs) is steadily increasing, new therapies are urgently needed to prolong the overall survival of patients. Objective This study aimed to identify diagnostic and therapeutic candidate markers for SBNETs. Methods Expression profiles of miRNAs were collected from GSE70534, and GSE103317, that of mRNAs were collected from GSE65286. Differentially expressed genes (DEmiRs, DEmRs) were analyzed between SBNETs and controls. Enrichment and coexpression analyses were carried out for DEmRs. XGBoost algorithm was used to screening feature miRNAs. Module genes in SBNETs-related pathways were selected to construct regulated network for feature miRNAs. Drug targeting prediction and immune environment evaluation were identified. Results A total of 57 common DEmiRs with the same direction of expression were identified. Hsa − miR − 375, hsa − miR − 107, hsa − miR − 1180, hsa − miR − 330 − 3p, and hsa − miR − 328 were identified as feature miRNAs. Among the target genes of feature miRNAs, PDPK1 was the correlation between PDPK1 and the target of Lutetium-177 (177Lu)-DOTATATE was the largest, which were regulated by miR − 375. Additionally, PDPK1 showed correlations with eosinophils, cytotoxic cells, and checkpoints in SBNETs. Conclusions Five feature miRNAs may have a good diagnostic role for the SBNETs. MiR − 375 regulated PDPK1 may serve as an effective therapeutic candidate marker for SBNETs.